Renewable Energy Approach with Indonesian Regulation Guide Uses Blockchain-BIM to Green Cost Performance - Albert E. Husin; Priyawan Priyawan; Bernadette D. Kussumardianadewi; Rizkiawan Pangestu; Riza S. Prawina; Kristiyanto Kristiyanto; Eka Juni Arif (Civil Engineering Journal, 2023)
Climate change is a threat and crisis that hit the world today; one of them is causing drought, rising sea levels, melting polar ice, and heat waves; therefore, the target towards Net Zero Emission (NZE) in 2060 must be an obligation in all countries. Green Building (GB) is a building that meets Building Technical Standards, and has demonstrated demonstrable success in conserving resources such as water, energy, and other resources. The application of GB principles following the function and classification in every stage of their implementation is expected to reduce greenhouse gas emissions. This research aims to analyze the cost of improvement work based on GB assessment in applying the Technical Guidelines from Minister of Public Works and Public Housing (PUPR) No. 1 of 2022, which is the latest regulation in Indonesia. The blockchain-BIM method and the implementation of the GB component will be analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to find the most influential factors. The results of this study show that by applying Blockchain-BIM to overcome the cost constraints, it is proven to be able to increase the cost performance of GB in modern shopping center buildings by 3–3.8% in the Basic rating, while for other ratings, it is 0.5–2.1% higher, where the selection of a renewable energy model is very influential. Doi: 10.28991/CEJ-2023-09-10-09 Full Text: PDF